Implementation of inter- and transdisciplinary concepts in art education at higher education: Implementasi konsep inter- dan transdisiplin dalam pendidikan seni rupa di perguruan tinggi - Kurniawati, Rizki Dwi; Prasetyo, Didi Yudha; Santi, Dhira; Wulandari, Dwi; Putra, Hilmy Aditama Surya (Sungging: Journal of Innovative, Cultural, Transdisciplinary Art and Kriya Discourse, 2025)
Contemporary visual arts education requires a holistic approach. This study examines the implementation of interdisciplinary and transdisciplinary approaches in visual arts education at a university in Yogyakarta. The research employs a qualitative phenomenological approach, conducted through in-depth interviews with lecturers. The findings show that these approaches have been applied sporadically, particularly in research-based projects and cross-disciplinary collaborations, but face challenges such as curriculum limitations, lecturer resistance, and students' low literacy. Strategies such as research mentoring, topic-based assignments, and the use of technology have been found to be effective. The study concludes that there is a need for the development of a flexible curriculum, lecturer training, and supporting infrastructure to optimise interdisciplinary and transdisciplinary approaches. _______________________________________________________________________________   Pendidikan seni rupa kontemporer membutuhkan pendekatan holistik. Penelitian ini mengkaji penerapan pendekatan interdisiplin dan transdisiplin di Pendidikan Seni Rupa di salah satu perguruan tinggi di Yogyakarta. Metode penelitian menggunakan pendekatan kualitatif fenomenologi melalui wawancara mendalam dengan dosen. Hasil penelitian menunjukkan bahwa pendekatan ini telah diterapkan secara sporadis, terutama dalam proyek berbasis riset dan kolaborasi lintas bidang, namun menghadapi tantangan seperti keterbatasan kurikulum, resistensi dosen, dan minimnya literasi mahasiswa. Strategi seperti pendampingan riset, tugas berbasis topik kompleks, dan pemanfaatan teknologi dianggap efektif. Penelitian ini menyimpulkan perlunya pengembangan kurikulum fleksibel, pelatihan dosen, dan infrastruktur pendukung untuk mengoptimalkan pendekatan interdisiplin dan transdisiplin.